Future network experiment platform based on SDN/NFV - Liang WEI; Rong LI; Zhengdong WU; Yuliang ZHANG; Zhiwei CHENG; Tao HUANG (Dianxin kexue)
According to the characteristics of SDN/NFV,the future network experiment platform based on SDN/NFV was proposed.The open source architecture of OpenStack and OpenDaylight was used,and the SDN cross-domain communication system,virtual network element management and network service orchestration were researched.Real-time dynamic management and effective sharing of the underlying heterogeneous resources were achieved.At the same time,according to the needs of the experimental users of the network resources,various network resources and SFC service was flexibly orchestrated and end-to-end network experimental verification services were provided to users.